Mirror Readmission Study of the Association of Electroconvulsive Therapy With 1-Year Mood Disorder Readmissions in a Tertiary Mood Disorder Unit. Issue 2 (June 2020) - Tor, Phern-Chern; Bin Abdin, Edimansyah
Abstract : Objectives: Electroconvulsive therapy (ECT) is one of the most effective treatments for severe mood disorders and may reduce psychiatric readmissions. However, the effect on ECT on mood disorder readmissions in Asia is unclear. We embarked to assess the relationship between inpatient ECT and 1-year psychiatric readmissions for patients with mood disorders. Methods: A retrospective database analysis of patients admitted to a tertiary Mood Disorders Unit in a developed Asian city was analyzed to investigate the association of inpatient ECT with psychiatric readmission using a 1-year mirror-image method with major depressive disorder and bipolar mania patients acting as their own controls. Covariates of age, sex, number of outpatient visits, and outpatient ECT were analyzed to account for confounders. t Tests were done to compare number and duration of psychiatric admissions and significance set at P < 0.05. Results: Patients with major depressive disorder and bipolar mania (N = 121) receiving inpatient ECT had a 35% mean reduction from the baseline mean of number of admissions in the 1-year after ECT. Maintenance ECT (between 30 days and 1 year after discharge) was associated with the protective effect ( β = −0.116, t = −2.044, P = 0.043). In major depressive disorder, there was a trend association between the number of 1-year postdischarge outpatient visits and decreased 1-year readmissions with an opposite association seen in bipolar mania. Conclusions: Electroconvulsive therapy may be associated with decreased 1-year readmissions for mood disorders in Asia, and this effect may be mediated by maintenance ECT.